HAMBATAN LEMBAGA PERS MAHASISWA IDEALITA SEBAGAI MEDIA EKSISTENSI KAMPUS - Angeline, Shintya; Nupiah, Ali (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The research motivated by the lack of effectiveness of the Idealita student press as one of the campus media at UIN Mahmud Yunus Batusangkar. This is evident from the infrequent journalistic activities conducted by the Idealita student press, such as irregular coverage schedules. Additionally, the distribution of journalistic works produced by the Idealita student press is also limited, and many students are unaware of the journalistic products created by Idealita. The aim of this research is to identify the internal and external constraints faced by the Idealita student press as a medium for campus existence at UIN Mahmud Yunus Batusangkar. The research adopted qualitative approach with a descriptive method. Data is collected through observation, interviews with 6 informants, and documentation. The data is then summarized and analyzed to draw conclusions. The data validity is researchers use source and technique triangulation. Based on the research conducted by the researchers, the internal obstacles of the Idealita student press institution as a campus presence medium are observed from the low motivation of members, ineffective communication, inadequate recruitment and selection systems, insufficient member training, as well as inadequate institution management and timing. On the other hand, the external obstacles of the Idealita student press institution as a campus presence medium are insufficient funding, resulting in a lack of resources and facilities provided by Idealita for coverage and writing processes.